Quasi-simultaneous observations of radio and X-ray variability in three radio-quiet Seyfert galaxies. Issue 2 (12th July 2022) - Chen, Sina; Laor, Ari; Behar, Ehud
ABSTRACT: Radio variability in some radio-quiet (RQ) active galactic nuclei suggests emission from regions close to the central engine, possibly the outer accretion disc corona. If the origins of the radio and the X-ray emission are physically related, their emission may be temporarily correlated, possibly with some time delays. We present the results of quasi-simultaneous radio and X-ray monitoring of three RQ Seyfert galaxies, Mrk 110, Mrk 766, and NGC 4593, carried out with the Very Large Array at 8.5 GHz over a period of about 300 d, and with the Rossi X-ray Timing Explorer at 2–10 keV over a period of about 2000 d. The radio core variability is likely detected in the highest resolution (A configuration) observations of Mrk 110 and NGC 4593, with a fractional variability amplitude of 6.3 per cent and 9.5 per cent, respectively. A cross-correlation analysis suggests an apparently strong (Pearson r  = −0.89) and highly significant correlation ( p  = 1 × 10 −6 ) in Mrk 110, with the radio lagging the X-ray by 56 d. However, a further analysis of the r values distribution for physically unrelated long time delays reveals that this correlation is not significant. This occurs since the Pearson correlation assumes white noise, while both the X-ray and the radio light curves follow red noise, which dramatically increases the chance, by a factor of ∼10 3, to get extremely high r values in uncorrelated data sets. A significantly longer radio monitoring with a higher sampling rate, preferably with a high-resolution fixed radio array, is required in order to reliably detect a delay.